2014
DOI: 10.1890/13-0412.1
|View full text |Cite
|
Sign up to set email alerts
|

Specific leaf area responses to environmental gradients through space and time

Abstract: Plant communities can respond to environmental changes by altering their species composition and by individuals (within species) adjusting their physiology. These responses can be captured by measuring key functional traits among and within species along important environmental gradients. Some anthropogenic changes (such as fertilizer runoff) are known to induce distinct community responses, but rarely have responses across natural and anthropogenic gradients been compared in the same system. In this study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
141
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(164 citation statements)
references
References 43 publications
(43 reference statements)
12
141
4
1
Order By: Relevance
“…Our results highlight that taking temporal intraspecific variations of traits into consideration may lead to different and interesting findings. If traits measured in a wet year were used to calculate functional indices for communities in a dry year, conclusions might be misleading (Dwyer et al, 2014). In the future, a long-term study on both CWM and FDis is required.…”
Section: Mechanisms Of Functional Diversity Variationmentioning
confidence: 99%
“…Our results highlight that taking temporal intraspecific variations of traits into consideration may lead to different and interesting findings. If traits measured in a wet year were used to calculate functional indices for communities in a dry year, conclusions might be misleading (Dwyer et al, 2014). In the future, a long-term study on both CWM and FDis is required.…”
Section: Mechanisms Of Functional Diversity Variationmentioning
confidence: 99%
“…We also used the same traits to predict the probability that individual species will either decrease or increase under the treatments. We chose these traits because they are strongly linked to nutrient and water use (36,38,43,44).…”
Section: Significancementioning
confidence: 99%
“…Variation among species in mean specific leaf area (SLA; leaf area/dry mass; or its inverse, termed leaf mass per unit area) has been found to correlate well with among-species variation in key physiological attributes such as leaf longevity (LL), water use efficiency (WUE), and relative growth rate (RGR). Species with high SLA and RGR, and low LL and WUE, are more prevalent in wetter climates (34) and in wetter years (35) and tend to increase disproportionately in response to experimental watering (36) and natural precipitation increase (37). Several previous studies have found that high-SLA species are especially vulnerable to decline or loss under aridification (38,39).…”
mentioning
confidence: 97%